p38 promoted retinal micro-angiogenesis through up-regulated RUNX1 expression in diabetic retinopathy - Zou, Wenjun (Biosci Rep, 2020)
Diabetic retinopathy (DR) is the most common microvascular complication of diabetes and is characterized by visible microvascular alterations including retinal ischemia–reperfusion injury, inflammation, abnormal permeability, neovascularization and macular edema. Despite the available treatments, some patients present late in the course of the disease when treatment is more difficult. Hence, it is crucial that the new targets are found and utilized in the clinical therapy of DR. In the present study, we constructed a DR animal model and a model in HRMECs to investigate the relationship between p38 and RUNX1 in retinal micro-angiogenesis in diabetic retinopathy. We found that p38 could promote retinal micro-angiogenesis by up-regulating RUNX1 expression in diabetic retinopathy. This suggested that the p38/ RUNX1 pathway could become a new retinal micro-angiogenesis target in DR treatment.